Rahn syariah: Urgensi gadai dalam membangun ekonomi umat yang sejahtera - ismayana, winda (Maliki Interdisciplinary Journal, 2025)
Many people are looking for funding solutions that are easy and in accordance with religious principles as people’s financial needs become more complex in this day and age. An increasingly popular solution for Muslims is Rahn Syariah, or Islamic pawn. The purpose of this study is to gain a better understanding of the concept, legal basis, pillars and conditions of Rahn Syariah, as well as its benefits for building a prosperous people’s economy. This research collects data and information from various literature sources. In addition, Islamic money can help Muslims in fulfilling their needs, improving access to capital, encouraging entrepreneurship, and improving their knowledge of Islamic finance.